Gambaran Faktor Predisposisi, Pemungkin dan Penguat terhadap Pemberian Imunisasi Dasar Lengkap di Kota Pariaman - Prima Yoselina; Meri Neherta; Lili Fajria; Rika Sabri; Deswita Deswita; Ira Mulya Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Immunization has decreased worldwide, especially during the covid-19 pandemic. The decline was caused by doubts and refusal to immunize, fear of parents, and limited access to health services. Immunization is one of the basic needs for children to grow and develop and prevent the emergence of new infectious diseases in children. This study is an observational study with a descriptive approach to determine the description of maternal predisposing, enabling, and reinforcing factors to basic immunization in Pariaman City. The population in this study amounted to 253 mothers and a sample of 154 mothers who had children aged 12 months using a simple random sampling technique. The results showed that the mother's age was 30 years (51.7%), the mother's education was high (82.5%) and the mother did not work (70.8%). The mother's knowledge is mostly lacking (40.3%), the mother's attitude is not supportive (56.5%) and the mother's trust is less (42.9%). The affordability of health resources is not affordable (52.6%), family support is not supportive (48.1%), health worker support is lacking (5.8%) and support from community leaders is not supportive (43.5%). It is hoped that nurses can provide optimal counseling and family motivation to provide support to mothers in providing complete basic immunizations for children